Preparation and Quality Assessment of Fruit Yoghurt with Persimmon (Diospyros kaki): Quality assessment of fruit yoghurt with persimmon - Khatoon, Nafeesa; Ali, Sartaj; Liu, Nan; S. Muzammil, Hafeez (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Yoghurt is a fermented dairy product developed by fermentation of milk with Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus. Assimilation of fruit pulp can boost the nutritional and health benefits of the yoghurt to many folds. The prime objective of preparing fruit yoghurt with the addition of persimmon pulp was to enhance the nutritional value and to improve overall acceptance. Yoghurt was prepared with the incorporation of persimmon in the concentration of 5%, 10% & 15% to assess the best combination. Evaluation of physico-chemical and organoleptic properties was performed during storage. The product was stored for 28 days at 4o C and quality parameters were assessed at an interval of 7 days. Acidity, total solids, and moisture content of fruit yoghurt increased while pH, lactose, protein, fat and textural profile values decreased significantly (p < 0.01) during storage. The phenolic content of the controlled sample was 175 mg GAE/g, which increased to 180, 214 and 250 mg GAE/g with 5%, 10% & 15% persimmon combinations respectively. Syneresis value for controlled sample was 2.49% which decreased to 2.45%, 1.94% & 1.10% in 5, 10 & 15% persimmon blends. Additionally, the sensorial properties of yoghurt blended with 10% fruit pulp gained higher acceptability during storage at 4o C.